Host Immunity and Inflammation to Pulmonary Helminth Infections - Weatherhead, Jill E.; Gazzinelli-Guimaraes, Pedro; Knight, John M.; Fujiwara, Ricardo; Hotez, Peter J.; Bottazzi, Maria Elena; Corry, David B. (Frontiers in Immunology, 2020)
Helminths, including nematodes, cestodes and trematodes, are complex parasitic organisms that infect at least one billion people globally living in extreme poverty. Helminthic infections are associated with severe morbidity particularly in young children who often harbor the highest burden of disease. While each helminth species completes a distinct life-cycle within the host, several helminths incite significant lung disease. This impact on the lungs occurs either directly from larval migration and host immune activation or indirectly from a systemic inflammatory immune response. The impact of helminths on the pulmonary immune response involves a sophisticated orchestration and activation of the host innate and adaptive immune cells. The consequences of activating pulmonary host immune responses are variable with several helminthic infections leading to severe, pulmonary compromise while others providing immune tolerance and protection against the development of pulmonary diseases. Further delineation of the convoluted interface between helminth infection and the pulmonary host immune responses is critical to the development of novel therapeutics that are critically needed to prevent the significant global morbidity caused by these parasites.